Yoga and South Asian spiritual paths: an introduction to Sikh studies in Latin America - Santos Ribeiro de Oliveira, Mirian (2019)
This paper interprets the travelogue Sikhs in Latin America: Travels Among the Sikh Diaspora, by Swarn Singh Kahlon, an Indian who travelled around Latin America between 2005 and 2006. The main goal of this work is analyzing the author’s perceptions on the experiences of adoption and keeping of the religious identity by new followers of Sikh religion, such as Kundalini Yoga practitioners. Primary sources presented by the author (such as interviews), by Sikh converts and by the Indian press were examined through content analysis. A literature review of academic works in the fields of travel writing studies, Indian studies, and, more specifically, Sikh studies, was undertaken. Highlighted research outcomes are: reflection on belongingness to Sikh communities in diasporic contexts; construction of a historical overview of Sikh presence in Latin America; analysis of narratives on Sikh identity enunciated by Latin American converts.